2017
DOI: 10.1111/aab.12383
|View full text |Cite
|
Sign up to set email alerts
|

Novel phytoplasma strains of X‐disease group unveil genetic markers that distinguish North American and South American geographic lineages within subgroups 16SrIII‐J and 16SrIII‐U

Abstract: Phytoplasmas in the X‐disease group (16SrIII) are highly diverse in terms of geographic distributions, vectorship and plant host specificity. Such biological and ecological diversity is often correlated with distinctive genetic markers present in evolutionarily conserved genes. Based on restriction fragment length polymorphism (RFLP) markers in the 16S rRNA gene sequences, 29 subgroups have been delineated, with most of them being found in the Americas. However, it has been unknown whether distinct geographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, subgroup 16SrIII-U has mainly been found to be associated with herbaceous plants, including solanaceous crops, and was thought to be restricted to South America. However, Pérez-López et al [ 55 ] recently reported variants of this subgroup from North America and also suggested a broader distribution. Our results further support this hypothesis with new detection in other biogeographic regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, subgroup 16SrIII-U has mainly been found to be associated with herbaceous plants, including solanaceous crops, and was thought to be restricted to South America. However, Pérez-López et al [ 55 ] recently reported variants of this subgroup from North America and also suggested a broader distribution. Our results further support this hypothesis with new detection in other biogeographic regions.…”
Section: Discussionmentioning
confidence: 99%
“…The 16SrIII-J phytoplasma is mainly reported in South America and Mexico [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In Chile, historically, this phytoplasma has been detected in sugar beet [ 19 ]; however, it is now described as infecting a wide range of herbaceous and woody plant species [ 10 , 20 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mexican strains of the subgroup 16SrIII-U, consistently distinguishable from their South American counterpart based on molecular markers, may represent emerging or previously unknown North American geographic lineages of the 16SrIII-U subgroup (Perez-Lopez et al, 2017) Are detection and identification methods available for the pest?…”
Section: Intraspecific Diversitymentioning
confidence: 99%
“…These are Clover yellow edge (CYE), belonging to the 16SrIII-B subgroup (Girsova et al, 2016), the North American Potato purple top (AKpot7, MT117, AKpot6), belonging to 16SrIII-F, -M, -N (Davis et al, 2013), and the Mexican Potato purple top (PPT-COAHP, PPT-GTOP), belonging to the 16SrIII-U subgroup (Santos-Cervantes et al, 2010). Assignment of the Mexican Potato purple top isolates to 16SrIII-U subgroup is uncertain as available 16S rRNA gene sequences are of insufficient length for definitive classification (Perez-Lopez et al, 2017). The Clover yellow edge phytoplasma is listed as [PHYP19] in EPPO GD (EPPO, 2020)…”
Section: Identity and Taxonomymentioning
confidence: 99%
See 1 more Smart Citation